Effect of sildenafil on human aromatase activity: From in vitro structural analysis to catalysis and inhibition in cells. Issue 165 (January 2017) - Baravalle, Roberta; Valetti, Francesca; Catucci, Gianluca; Gambarotta, Giovanna; Chiesa, Mario; Maurelli, Sara; Giamello, Elio; Barone, Ines; Catalano, Stefania; Andò, Sebastiano; Di Nardo, Giovanna; Gilardi, Gianfranco
Graphical abstract: Highlights: Human aromatase binds the drug sildenafil showing a Type II spectrum. EPR spectroscopy shows that sildenafil does not directly bind heme iron. Sildenafil acts as a mixed and partial inhibitor on human aromatase. Aromatase inhibition by sildenafil is confirmed in ST14A and MCF-7 cells. Abstract: Aromatase catalyses the conversion of androgens into estrogens and is a well-known target for breast cancer therapy. As it has been suggested that its activity is affected by inhibitors of phosphodiesterase-5, this work investigates the potential interaction of sildenafil with aromatase. This is carried out both at molecular level through structural and kinetics assays applied to the purified enzyme, and at cellular level using neuronal and breast cancer cell lines. Sildenafil is found to bind to aromatase with a KD of 0.58 ± 0.05 μM acting as a partial and mixed inhibitor with a maximal inhibition of 35 ± 2%. Hyperfine sublevel correlation spectroscopy and docking studies show that sildenafil binds to the heme iron via its 6th axial water ligand. These results also provide information on the starting molecular scaffold for the development of new generations of drugs designed to inhibit aromatase as well as phosphodiesterase-5, a new emerging target for breast cancer therapy.